The absorption and desorption characteristics of mansuli bentonite - Nur Syahida, Mohamed @ Mohd Junid (2016)
Moisture content of a soil is defined by water content in the specific soil. It is important to know the water content in soil in order to find the characteristics . Due to the type of ions contained, the level of hydration and swelling will varies. This study focus on the determination of absorption and desorption of Mansuli Bentonite clay. Appropriate suction methods, wetting and drying process using Vapour Equilibrium Technique and the second method, Chilled Mirror Device were used in this study. The hysteresis effect in the water potential-water content relation is obtained under wetting and drying process, where hysteresis is the difference in the relationship between the water content of the soil and the corresponding water potential. The compared results of both methods by using soil-water characteristics curve (SWCC) shows that Mansuli Bentonite has a very high soil suction. In general, this study shows that the reading of soil suction of Mansuli Bentonite from both method is almost the same. With different levels of water content, soil suction will varies. The higher water content in Mansuli bentonite result with lower soil suction.